If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1)(x + 3) = 4 Reorder the terms: (-1 + x)(x + 3) = 4 Reorder the terms: (-1 + x)(3 + x) = 4 Multiply (-1 + x) * (3 + x) (-1(3 + x) + x(3 + x)) = 4 ((3 * -1 + x * -1) + x(3 + x)) = 4 ((-3 + -1x) + x(3 + x)) = 4 (-3 + -1x + (3 * x + x * x)) = 4 (-3 + -1x + (3x + x2)) = 4 Combine like terms: -1x + 3x = 2x (-3 + 2x + x2) = 4 Solving -3 + 2x + x2 = 4 Solving for variable 'x'. Reorder the terms: -3 + -4 + 2x + x2 = 4 + -4 Combine like terms: -3 + -4 = -7 -7 + 2x + x2 = 4 + -4 Combine like terms: 4 + -4 = 0 -7 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '7' to each side of the equation. -7 + 2x + 7 + x2 = 0 + 7 Reorder the terms: -7 + 7 + 2x + x2 = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 2x + x2 = 0 + 7 2x + x2 = 0 + 7 Combine like terms: 0 + 7 = 7 2x + x2 = 7 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 7 + 1 Reorder the terms: 1 + 2x + x2 = 7 + 1 Combine like terms: 7 + 1 = 8 1 + 2x + x2 = 8 Factor a perfect square on the left side: (x + 1)(x + 1) = 8 Calculate the square root of the right side: 2.828427125 Break this problem into two subproblems by setting (x + 1) equal to 2.828427125 and -2.828427125.Subproblem 1
x + 1 = 2.828427125 Simplifying x + 1 = 2.828427125 Reorder the terms: 1 + x = 2.828427125 Solving 1 + x = 2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 2.828427125 + -1 Combine like terms: 1 + -1 = 0 0 + x = 2.828427125 + -1 x = 2.828427125 + -1 Combine like terms: 2.828427125 + -1 = 1.828427125 x = 1.828427125 Simplifying x = 1.828427125Subproblem 2
x + 1 = -2.828427125 Simplifying x + 1 = -2.828427125 Reorder the terms: 1 + x = -2.828427125 Solving 1 + x = -2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -2.828427125 + -1 Combine like terms: 1 + -1 = 0 0 + x = -2.828427125 + -1 x = -2.828427125 + -1 Combine like terms: -2.828427125 + -1 = -3.828427125 x = -3.828427125 Simplifying x = -3.828427125Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.828427125, -3.828427125}
| 167=6+7(2-7x) | | ln(2x+1)+ln(x-1)=lnx | | 0.0058x^2-0.67x+15.2=-3 | | 36i^2+16i+36=0 | | (2x)(x+2)=52 | | z^2-6iz-9+4i=0 | | f(x)=2x^2-8x-1 | | 525.00+0.21x+585.00+0.13x= | | 7ln(2x)=21 | | 9x(x-8)=y-3 | | 5+1z=17 | | 8(3)=4(x-1) | | -0.9x-0.6(2)=2.3 | | p(x)=3x^3+32x^2+32x+27 | | -0.9(2)-0.6y=2.3 | | x-0.4x=186 | | 9x-2(1)=-37 | | 9(1)-2y=-37 | | 4+2y-2=8y+9-5y | | 3(x-3)=5(1.5x+x) | | 27x^2+32x=52 | | 5y=-x | | -2(1)+12y=47 | | 3r-q=2 | | 3q-r=2 | | -2x+12(1)=47 | | 8(t-5)+4t=4(3t+5)-13 | | 8x+90=2x+32 | | 4(3x-4)+23=12 | | (p^2-5p+4)=0 | | -5(2t-2)+8t=4t-7 | | 2x^2+14x-20= |